STARTEGI PENGELOLAAN PRODUKSI SIARAN â€˜DJ SHOWâ€™ RADIO PRAMBORS MAKASSAR DI ERA MEDIA KONVERGENSI - Dh Pasha, Sartika Sari Wardanhi; Rezkiawaty, Sitti Utami (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2020)
ABSTRACT The Prambors radio â€œDJ SHOWâ€ broadcast program is currently the only local program that is broadcasted simultaneously on 9 Prambors radio networks (Jakarta, Bandung, Solo, Semarang, Jogjakarta, Surabaya, Medan, Manado, and Makassar). Facing challenges in the era of media convergence, the local Prambors radio program team especially Makassar in collaboration with Network Brodacst Coordinator runs broadcast production management by not only focusing on activities carried out inside or outside the broadcast room but also synergizing with digital media in exposing all forms of creative content, hits music or advertisements that are part of this program. The purpose of this research was to identify the strategy in managing the production of DJ SHOW of Radio Prambors Makassar in the era of convergence media. This research used descriptive qualitative research methods by collecting data through observation and interviews. The theory used in this research was management theory by George R. Terry, which explains the processes in broadcasting management in several stages, namely planning, organizing, actuating, and evaluating/controlling. The findings of this study were that the broadcast program team applied three main pillars namely on-air, off-air, and also online. Maximizing the use of new media, especially social media in the implementation of broadcast programs, has a very significant impact on increasing the amount of interaction and engagement with listeners on social media.Â Keywords: Broadcast Production Management Strategy, Radio, Social Media, Media Convergence